The Role of the Key Images in the Creation and Enhancement of the Pragmatic Potential of the Text - Mariana Sargsyan (Armenian Folia Anglistika, 2014)
The present paper argues that the qualitative and quantitative aspects of the text pragmatics can be enhanced at the expense of stylistic devices. Particularly, the case of simile is considered with a view to exposing the pragmatic potential of the key images embedded therein. In line with our research goals, with the account of internal and external factors underlying the choice and application of language units, the pragmatic and pragmastylistic potential of the chosen units in the creation and enhancement of text pragmatics is revealed.